Pengaruh School Well-Being terhadap Motivasi Belajar Siswa di Madrasah Aliyah Ma'arif 7 Sunan Drajat Lamongan - Muhimmatul Hasanah; Sutopo (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
The purpose of the study was to determine the effect of school well-being on student motivation at Madrasah Aliyah Ma’arif 7 Sunan Drajat Lamongan. The hypothesis proposed is that there is an effect of school well-being on student motivation at Madrasah Aliyah Ma’arif 7 Sunan Drajat Lamongan. The subjects in this study were 150 students at Madrasah Aliyah Ma’arif 7 Sunan Drajat Lamongan. Taking the subject using purposive sampling technique. The data collection technique uses a school well-being level measurement tool and a learning motivation measurement tool that is arranged with a modified likert scale model. The analysis technique used to analized the data in this study is Simple Linier Regression with SPSS statistical programe. The result showed that the value of R square or the coefficient of determination was 0,565 from school well-being variable. The R square value of 0,565 indicate the effect of the independent variable (school well-being) on the dependent variable (learning motivation) of 56,5% while the remaining 43,5% is influenced by other variabels not examined.